Obesity as a risk factor for poor outcomes after sling surgery in women with stress urinary incontinence: A systematic review and meta‐analysis. Issue 8 (14th August 2020) - Barco‐Castillo, Catalina; Plata, Mauricio; Zuluaga, Laura; Serrano, Adolfo; Gómez, Andrea; Santander, Jessica; Caicedo, Juan I.; Azuero, Julián; Echeverry, Mariana; Trujillo, Carlos Gustavo
Abstract: Purpose: Obesity is one of the main risk factors for stress urinary incontinence (SUI) and has also been associated with worse surgical outcomes. However, the literature is heterogeneous and inconclusive. The goal of this study was to perform a systematic review and meta‐analysis to evaluate cure rates and perioperative complications in obese women. Materials and Methods: A literature search of OVID, MEDNAR, Embase, Scopus, Web of Science, PubMed, and CENTRAL databases was conducted. Randomized controlled trials comparing cure rates and failure of treatment in normal and obese patients, who underwent mid‐urethral sling surgery, were identified. A systematic review of subjective and objective cure rates, and complications was performed. Meta‐analyses of dichotomous data under the random‐effects model were applied using Review Manager 5.3. Nonrandomized comparative studies and gray literature were excluded. Results: A total of 219 studies were identified. Four randomized controlled trials were included for evaluation. The risk of bias evaluation was performed according to the Cochrane Handbook for Systematic Reviews of Interventions. One study was excluded due to missing data on the outcomes. Patients were stratified according to their body mass index as obese (>30 kg/m 2 ) and nonobese (<30 kg/m 2 ). Complications could not be meta‐analyzed. The meta‐analysis of subjective (risk ratio [RR] = 1.69 [95% confidence interval [CI]: 1.32‐2.16]) and objective (RR = 1.62 [95% CI: 1.26‐2.07]) cure rates disfavored obese women. Conclusions: This meta‐analysis shows that obesity is a risk factor for the nonsuccessful treatment of SUI with tension‐free mid‐urethral sling. Differences in regards to the surgical approach and its association with obesity could not be established with the current evidence.